2004
DOI: 10.1213/01.ane.0000136770.75805.19
|View full text |Cite
|
Sign up to set email alerts
|

The Postoperative Blood-Sparing Efficacy of Oral Versus Intravenous Tranexamic Acid After Total Knee Replacement

Abstract: To assess the blood-sparing efficacy of tranexamic acid (TA) administered orally or via a variable IV infusion, 80 healthy patients undergoing elective total knee replacement were studied according to a prospective, controlled, randomized, single-blinded study design. Patients were allocated to one of four treatment groups. In group TA-long, 30 min before deflation of the limb tourniquet, an IV bolus dose of TA 15 mg/kg was administered over 30 min. Thereafter, a constant IV infusion of 10 mg . kg(-1) . h(-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 9 publications
8
120
1
2
Order By: Relevance
“…Zohar et al (27) implants (30)(31)(32)(33) and favored based on the concern that systematic administration of IV-TXA might potentially increase the risk of thrombosis (34). In contrast, the TEG data obtained in the current study suggest that IV-TXA did not promote hypercoagulation since the mean CI in the TXA and FS + TXA groups was less than +3 and this CI remained similar to that of the control group during hospitalization.…”
Section: Discussioncontrasting
confidence: 49%
“…Zohar et al (27) implants (30)(31)(32)(33) and favored based on the concern that systematic administration of IV-TXA might potentially increase the risk of thrombosis (34). In contrast, the TEG data obtained in the current study suggest that IV-TXA did not promote hypercoagulation since the mean CI in the TXA and FS + TXA groups was less than +3 and this CI remained similar to that of the control group during hospitalization.…”
Section: Discussioncontrasting
confidence: 49%
“…Similar to their hemoglobin findings, both Irwin and Fillingham found comparable transfusion rates (<10%) between IV and oral TXA. Zohar, one of the first authors to study oral TXA in total joint surgery found a significant decrease in transfusion rates between placebo and oral TXA groups and Bradshaw's prospective study of oral TXA in total knee arthroplasty found no transfusions in the TXA group [33,35]. The literature remains somewhat unclear however.…”
Section: Oral Usementioning
confidence: 99%
“…14 Oral TXA has been shown to decrease blood loss 2 and has similar efficiency as IV administration. 15 As the oral form of TXA is cheaper than the IV form, the financial benefit of oral TXA application has been reported as £2.04 (GB sterling) per patient. 16 Beside the relatively low cost of oral TXA, the simple application avoiding IV access is a further advantage reducing additional costs and avoiding expensive nursing care for IV application.…”
Section: Introductionmentioning
confidence: 99%